(untitled) (Biological Sciences - PJSIR, 2022)
samples were stored in high density polythene bags at -20°C until analysed. The Romer method [7,8] was followed for the quantification [8]. Relevant details of the procedure are gi ven in our earlier work [6]. Recovery of the aflatoxin by the standard addition method ranged between 97-101 %. Each estimation was performed in triplicate. Aflatoxin reference standards were obtained from Rijiks institute vwr volkgezondeheit, Bilthoven, Netherland.